Social skills and behavior in children during the dental appointment in a school teaching and dental assistance, Cartagena (Colombia) - Ketty Ramos-Martínez; Lizelia Margarita Alfaro-Zolá; Lesbia Rosa Tirado-Amador; Farith González-Martínez (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Introduction: the goal of this study was to describe the social skills, behavior, and related problems of children during dental consultation at a teaching care center in the city of Cartagena, Colombia. Methods: this was a cross sectional study in 205 children aged 5 to 8 years receiving dental treatment in the area of study and evaluated by the Frankl scale, the Preschool and Kindergarten Behavior Scales (PKBS), and a survey about family and socio-demographic factors. The analysis was performed by means of averages (±DE), t-tests, one-way analysis of variance (Anova), and Chi square tests. Results: the Frankl scale showed higher positive behaviors. The findings obtained in the social skills dimension for the “help a friend in trouble” item showed higher averages as age progressed: age 5 (1.46), age 6 (1.57), age 7 (1.74), age 8 (1.77) (p<0.03). There was a difference for the type of clinic where care was provided (p˂0.05). Concerning behavioral problems, some items showed differences in terms of age (p˂0.05), sex (p˂0.05), and type of clinic (p˂0.05). Conclusions: some environmental factors and personal relationships influence the social skills, behavior, and related problems in children.